Planning and financial literacy: How do women fare? - Annamaria Lusardi; Olivia S. Mitchell (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
Many older US households have done little or no planning for retirement, and there is a substantial population that seems to undersave for retirement. Of particular concern is the relative position of older women, who are more vulnerable to old-age poverty due to their longer longevity. This paper uses data from a special module we devised on planning and financial literacy in the 2004 Health and Retirement Study. It shows that women display much lower levels of financial literacy than the older population as a whole. In addition, women who are less financially literate are also less likely to plan for retirement and be successful planners. These findings have important implications for policy and for programs aimed at fostering financial security at older ages.
urn:nbn:de:hebis:30-52384
Keywords: D91; 330; Aging; Financial Literacy; Gender Issues; Alterssicherung; Sparen; Kapitalanlage; Wissen; Frauen; Armut; USA